Inclusion of land use changes in long‐term regional climate simulations over East Asia. (April 2017) - Zhao, Deming; Wu, Jian
Abstract: Long‐term simulations with regional climate models (RCMs) show biases over East Asia that result partly from fix‐in‐time land use data (EX2001). Using four satellite‐based land use images (EX8901) from the past 30 years instead of default values, 34‐year integrations were performed to make comparisons (EX8901 minus EX2001) over East Asian land areas. The decreased albedo (−0.019) resulted in weakened upward short‐wave flux, contributing to positive surface radiative forcing (2.89 W m −2 ), which then induced enhanced sensible heat fluxes. The near‐surface wind speed was weakened (−0.15 m s −1 ) in relation to the increased roughness length (0.042 m) and weakened pressure gradient, and induced a decreased precipitation bias of 0.0095 mm day −1 . The increased ground temperature and enhanced soil water content promoted strengthened sensible and latent heat fluxes, which induced a decreased surface air temperature bias (−0.24 °C). Results show that by including land use changes, model simulations can be improved.